KESALAHAN BERBAHASA PADA NASKAH DRAMA “AYAHKU PULANG” KARYA USMAR ISMAIL (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research was conducted to analyze language errors in the drama script "My Father Pulang" by Usmar Ismail, aiming to identify language errors in the areas of syntax and diction. Then this study describes the mistakes. The method used in this study uses a descriptive-qualitative method. This type of research makes descriptions, makes descriptions, which are factual and accurate with the data. Qualitative methods are used to provide descriptions and explanations that are very clear, objective, analytical, systematic, and critical of language errors in the drama script "My Father Pulang". As for the results of this study there are diction errors, errors in the use of excessive words, and errors in syntax. Diction errors are related to errors in word selection in drama script sentences so that the meaning is not quite right. Errors in the use of excessive words, namely words that are used less effectively in one sentence that has more meaning. While the syntax field errors with inappropriate prepositions and related to morphology.